Systemic Administration of Proteoglycan Protects BALB/c Retired Breeder Mice from Experimental Arthritis - Ishikawa, Larissa Lumi Watanabe [UNESP]; Colavite, Priscila Maria [UNESP]; Fraga-Silva, Thais Fernanda De Campos [UNESP]; Mimura, Luiza Ayumi Nishiyama [UNESP]; Franï¿½a, Thais Graziela Donegï¿½ [UNESP]; Zorzella-Pezavento, Sofia Fernanda Gonï¿½alves [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Marcolino, Larissa Doddi [UNESP]; Marques, Camila; Ikoma, Maura Rosane Valerio; Sartori, Alexandrina [UNESP] (Hindawi, 2016)
This study was undertaken to evaluate the prophylactic potential of proteoglycan (PG) administration in experimental arthritis. Female BALB/c retired breeder mice received two (2xPG50 and 2xPG100 groups) or three (3xPG50 group) intraperitoneal doses of bovine PG (50 μg or 100 μg) every three days. A week later the animals were submitted to arthritis induction by immunization with three i.p. doses of bovine PG associated with dimethyldioctadecylammonium bromide adjuvant at intervals of 21 days. Disease severity was daily assessed after the third dose by score evaluation. The 3xPG50 group showed significant reduction in prevalence and clinical scores. This protective effect was associated with lower production of IFN-γ and IL-17 and increased production of IL-5 and IL-10 by spleen cells restimulated in vitro with PG. Even though previous PG administration restrained dendritic cells maturation this procedure did not alter the frequency of regulatory Foxp3+ T cells. Lower TNF-α and IL-6 levels and higher expression of ROR-γ and GATA-3 were detected in the paws of protected animals. A delayed-type hypersensitivity reaction confirmed specific tolerance induction. Taken together, these results indicate that previous PG inoculation determines a specific tolerogenic effect that is able to decrease severity of subsequently induced arthritis.